2019
DOI: 10.3389/fnins.2019.00722
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Sustained Manual Pressure Stimulation According to Site of Action

Abstract: Sustained pressure stimulation of the body surface has been used in several physiotherapeutic techniques, such as reflex locomotion therapy. Clinical observations of global motor responses and subsequent motor behavioral changes after stimulation in certain sites suggest modulation of central sensorimotor control, however, the neuroanatomical correlates remain undescribed. We hypothesized that different body sites would specifically influence the sensorimotor system during the stimulation. We tested the hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 78 publications
3
17
0
Order By: Relevance
“…This necessitates an adequate control condition, e.g., a comparison between similar kinds of stimulation with or without known motor consequences. Therefore, several functional imaging studies contrasted the effects of therapeutic stimulation according to Vojta 25,26 with a sham stimulation 11,12,17 . Sanz-Esteban et al 17 applied pressure stimulus to an active site at the anterior thorax 25 and reported the main effect of the stimulation site (active versus control) in the ipsilateral putamen 17 .…”
Section: Evidence From Fmri and Pet Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…This necessitates an adequate control condition, e.g., a comparison between similar kinds of stimulation with or without known motor consequences. Therefore, several functional imaging studies contrasted the effects of therapeutic stimulation according to Vojta 25,26 with a sham stimulation 11,12,17 . Sanz-Esteban et al 17 applied pressure stimulus to an active site at the anterior thorax 25 and reported the main effect of the stimulation site (active versus control) in the ipsilateral putamen 17 .…”
Section: Evidence From Fmri and Pet Studiesmentioning
confidence: 99%
“…In our fMRI study of sustained manual pressure stimulation 12 , we compared an active lateral heel site at the right foot 26 to a nearby control lateral ankle site in 30 healthy volunteers who underwent two fMRI sessions according to a cross-over single-blinded randomised study design. To more closely match the characteristic postural conditions and prolonged manual stimulation during RLT (ref.…”
Section: Evidence From Fmri and Pet Studiesmentioning
confidence: 99%
See 3 more Smart Citations